Growth Allometry of Sweet Corn as Influenced by Tillage and Seaweed under Tarai Region of Nagaland - Kumari, Shivani; Tzudir, Lanunola; Merentoshi; Chishi, Hillel M.; Yosung, Lenmem; Malemnganbi, Takhelmayum; Zion, G.; Debbarma, John; Jamir, Zulutemjen; Lytan, Damitre; et al. (International Journal of Economic Plants, 2024)
A study was carried out at Crop Research Farm, Department of Agronomy, SAS, Nagaland University, Nagaland, India during kharif (May-September, 2021 and 2022) situated at 25° 45’ 3.68”N latitude and 93° 51’ 29.79” E longitude, to study the influence of tillage and seaweed extract on growth allometry of sweet corn under tarai region of Nagaland. The experiment was conducted in split plot design with two factor treatment and was replicated thrice. Factor one comprised of three tillage practices viz., conventional tillage, minimum tillage and zero tillage in the main plots and factor two included seven treatments consisting of seed priming followed by foliar spray of seaweeds i.e. Kappaphycus alvarezii and Sargassum wightii viz., water spray (control), K-Seaweed sap 5%, K-Seaweed sap 10%, K-Seaweed sap 15%, S-Seaweed sap 5%, S-Seaweed sap 10%, S-Seaweed sap 15%, in the sub-plots at 30, 50 and 70 days after sowing. Results of study revealed that significantly higher stem girth, leaf area, leaf area index, leaf area duration, SPAD meter reading at different intervals were noticed in conventional tillage. When seeds were treated with 10% S-Sap along with 10% S-Sap spray at three different intervals recorded significantly higher stem girth, number of functional leaves plant-1, leaf area, leaf area index, leaf area duration and chlorophyll index readings.